Using phosphine as an effective commodity fumigant - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Using phosphine as an effective commodity fumigant by R W D Taylor and I Gudrups 1996 14pp UKL5.00 ISBN 0 85954 437 0